Form Follows Faith: Swedish Architects, Expertise and New Religious Spaces in the Stockholm Suburbs. (1st October 2015) - Mack, Jennifer
In 2007, the City of Stockholm initiated the Järva Lift to remodel several 'segregated' suburbs, originally constructed during the state-sponsored 'Million Programme' (1965–1974). Recognizing the area's large immigrant population, the Lift proposed several new mosques; Spridd's Multicultural Centre, Johan Celsing's Rinkeby Mosque and a new building for the Stockholm Large Mosque Organization with collaboration from Tengbom are now planned. Here, I explore how these projects travel, both across domains of design expertise and through the planning regimes of the Swedish capital. Many constituents have origins in Somalia, yet architects from countries like Kuwait and Saudi Arabia have been asked to submit sketches, and Swedish architects have ultimately been hired to create or reshape designs that appeal to the local planning bureaucracy. Intriguingly, all three Swedish firms – ranging from boutique to corporate – have never before designed a mosque. Clients request intricate façade details or distinct interior spaces for men and women, moves that are considered 'un-Swedish' for formal and social reasons respectively. In response, two mosques are described as merging Muslim and Scandinavian design traditions, and one architect proposes the eventual disappearance of a mobile panelling system designed to separate worshippers of different genders. Has bureaucratic expertise trumped the design knowledge that a more seasoned mosque architect might bring?